The effectiveness of cytoprotection in the treatment of stable angina in patients with arterial hypertension and hyperuricemia, taking into account the peculiarities of the course of coronary artery disease in wartime - Iablonska, Victoriia; Kholopov, Leonid; Khyzhnyak, Olena; Batashova-Halinska, Viktoriia (ScienceRise: Medical Science, 2022)
The aim of the study is to establish the effectiveness of treatment of severe angina pectoris in patients with hyperuricemia, taking into consideration the peculiarities of the course of coronary artery disease (CAD) in wartime, using ranolazine – a selective inhibitor of the late sodium flow in combined pharmacotherapy. Materials and methods. We studied the anti-anginal effect of ranolazine in 14 patients with CAD, stable angina pectoris III-IV functional class (FC), hyperuricemia and arterial hypertension (AH) during 6 months of the 2022 year. The effectiveness of the study drug on the clinical course of angina pectoris was assessed by questionnaire and clinical examination after three months of treatment. The results. At the end of the second week of ranolazine use, angina attacks at rest, which were registered before the start of the observation, stopped in all patients with angina pectoris III FC and 50 % with angina pectoris IV FC. In 78.6 %, the number of angina attacks and the use of nitrates decreased by more than 2 times; 21.4 % no longer had angina attacks. At the end of the first month, anginal attacks were not observed in all patients with angina pectoris III FC and 50 % with angina pectoris FC IV. In 2 patients with angina pectoris IV FC (50 %), anginal attacks continued to be registered during physical exertion and emotional stress, but no more than once a week. At the same time, there were no angina attacks at rest. The same results were obtained during the survey of patients at the end of three months of observation. Conclusions. Ranolazine is an effective component of anti-anginal therapy, significantly affecting the patient's quality of life. Therefore, we can recommend ranolazine for patients with hyperuricemia in angina attacks that persist with insufficient effectiveness of zasic therapy with first-line drugs, especially during military conflicts